2017
DOI: 10.1002/2017jd026719
|View full text |Cite
|
Sign up to set email alerts
|

Mirrored changes in Antarctic ozone and stratospheric temperature in the late 20th versus early 21st centuries

Abstract: Observed and modeled patterns of lower stratospheric seasonal trends in Antarctic ozone and temperature in the late 20th (1979–2000) and the early 21st (2000–2014) centuries are compared. Patterns of pre‐2000 observed Antarctic ozone decreases and stratospheric cooling as a function of month and pressure are followed by opposite‐signed (i.e., “mirrored”) patterns of ozone increases and warming post‐2000. An interactive chemistry‐climate model forced by changes in anthropogenic ozone depleting substances produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 43 publications
(66 reference statements)
3
44
2
Order By: Relevance
“…Changes are considerably smaller in fall (brown). Similar covarying behavior between ozone and temperature changes in the lower stratosphere has recently been observed over Antarctica (Solomon et al, ).…”
Section: Ozone Recovery and Stratospheric Warmingsupporting
confidence: 80%
See 2 more Smart Citations
“…Changes are considerably smaller in fall (brown). Similar covarying behavior between ozone and temperature changes in the lower stratosphere has recently been observed over Antarctica (Solomon et al, ).…”
Section: Ozone Recovery and Stratospheric Warmingsupporting
confidence: 80%
“…The reversal from ozone depletion to ozone recovery is likely an important driver for the lower stratospheric temperature trends to switch from cooling to warming, as also emphasized by Maycock (2016) and Solomon et al (2017). Vertical trend profiles derived from radiosonde temperature data show maximum cooling before 2000 and maximum warming trends after 2000, predominantly at altitudes between 20 and 25 km (Figure 3).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Figure b shows a similar comparison of ozone changes in the Antarctic spring lower stratosphere, comparing September ozonesonde measurements from Syowa (69°S) with WACCM zonal means sampled at 70°S, motivated by similar comparisons in Solomon et al (). The time series show decreases prior to the late 1990s followed by increases after circa 2000, with reasonable agreement between the model and ozonesonde measurements (consistent with results in Solomon et al, , ). The comparisons in Figures a and b suggest accurate simulation of ozone changes (decrease and partial recovery) in WACCM for the two subperiods.…”
Section: Resultsmentioning
confidence: 68%
“…Regardless of precise significance levels, the characteristic spatial and temporal behavior of the observed trends, and congruence with the WACCM simulations, provides convincing evidence that healing of the ozone hole reported in Solomon et al () is being reflected in observed temperature trends for the Antarctic lower stratosphere. A similar conclusion regarding Antarctic temperature trends has been reported by Solomon et al (), based on (Modern‐Era Retrospective Analysis for Research and Applications‐2) MERRA2 reanalysis data. Overall, the observed temperature responses to stratospheric ozone changes, in both the lower and upper stratosphere, provide further evidence for anthropogenic influence on stratospheric temperatures.…”
Section: Discussionmentioning
confidence: 99%